2019
DOI: 10.1038/s41564-019-0510-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cryptic inoviruses revealed as pervasive in bacteria and archaea across Earth’s biomes

Abstract: Bacteriophages from the Inoviridae family (inoviruses) are characterized by their unique morphology, genome content and infection cycle. One of the most striking features of inoviruses is their ability to establish a chronic infection whereby the viral genome resides within the cell in either an exclusively episomal state or integrated into the host chromosome and virions are continuously released without killing the host. To date, a relatively small number of inovirus isolates have been extensively studied, e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
259
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(278 citation statements)
references
References 79 publications
4
259
1
Order By: Relevance
“…For contigs <3kb, taxonomic classification was set as "unclassified" because there are not enough predicted genes beyond the RT and DGR target on these contigs for a robust classification using the majority rule approach. Viral origin was predicted using a combination of VirSorter 45 v1.0.5 (as for genomes), the Earth's Virome pipeline 46 , and the inovirus detector pipeline 47 . All sequences identified as viral with the Earth's Virome pipeline, the inovirus detector pipeline, or VirSorter categories 1, 2, 4, and 5 were considered "viral", while sequences only predicted with VirSorter as categories 3 or 6 were listed as "putative viral" for the RT OTU-level aggregation (see below).…”
Section: Selection and Annotation Of Reference Genomes And Metagenomementioning
confidence: 99%
See 2 more Smart Citations
“…For contigs <3kb, taxonomic classification was set as "unclassified" because there are not enough predicted genes beyond the RT and DGR target on these contigs for a robust classification using the majority rule approach. Viral origin was predicted using a combination of VirSorter 45 v1.0.5 (as for genomes), the Earth's Virome pipeline 46 , and the inovirus detector pipeline 47 . All sequences identified as viral with the Earth's Virome pipeline, the inovirus detector pipeline, or VirSorter categories 1, 2, 4, and 5 were considered "viral", while sequences only predicted with VirSorter as categories 3 or 6 were listed as "putative viral" for the RT OTU-level aggregation (see below).…”
Section: Selection and Annotation Of Reference Genomes And Metagenomementioning
confidence: 99%
“…These high-quality target genes were clustered at 99% AAI using cd-hit 41 v4.8.1, then clustered in a two-step process as in ref. 47 . Briefly, sequences are first clustered using MCL 52 from an all-vs-all blastp, using blast score as edge weight and an inflation value of 2.0, then HMM profiles were built for these clusters and hhsearch 55 v3.1.0 was used to identify similarities between clusters.…”
Section: Clustering and Functional Annotation Of Predicted Target Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial advances in metagenomics and single-cell genomics have rapidly expanded known biodiversity by recovering sequences of 100s of thousands of uncultured bacteria and archaea from the environment and from the human microbiome ( Brown et al, 2015;Parks et al, 2017;Rinke et al, 2013;Schulz et al, 2017a) . Metagenomics has also recently proven to be a powerful method for assessing diversity and coding potential of environmental viruses (Paez-Espino et al, 2016;Roux et al, 2019) . Most viral genomes are small in size and when found in metagenomic data they are readily present on a single contig and thus often considered complete or near complete (Roux et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have recently reported that Pf phage influence the pathogenesis of P. aeruginosa infections in the lung and other environments by inducing liquid crystal biofilm and promoting chronic infection. [11,12,[15][16][17][20][21][22] For all of these reasons there is a pressing need for effective and reliable protocols for assessments of both phage and bacteria in CF sputum. [23,24] Respiratory secretions are primarily composed of polymeric mucins (MUC5AC and MUC5B) that form a gel like material with complex rheological properties that form the basis for its function as an innate defense barrier, including viscoelasticity, cohesiveness, adhesiveness and wetness.…”
Section: Introductionmentioning
confidence: 99%